The relationship between older adults' technology use, in-person engagement, and pandemic-related mental health. (2nd January 2023) - Drazich, Brittany F.; Li, Qiwei; Perrin, Nancy A.; Szanton, Sarah L.; Lee, Ji Won; Huang, Chien-Ming; Carlson, Michelle C.; Samuel, Laura J.; Regier, Natalie G.; Rebok, George W.; Taylor, Janiece L.
Abstract: Objective: The objectives of this study are to 1) describe changes in in-person communication/activity and changes in older adult technology use during the COVID-19 pandemic and 2) examine whether less in-person communication/activity mediates the relationship between pandemic-related mental health and technology use. Method: Linear regressions (stratified by age and financial strain) and structural equation modeling were employed using a nationally representative, cross-sectional survey of 3, 188 older adults from the 2020 National Health and Aging Trends Study's COVID-19 Questionairre. Results: Older adults engaged in more technology-based activity (b = 0.24; p<.001), more technology-based health care communication (b = 0.22; p<.001), and more technology-based food acquisition (b = 0.21; p<.001) during the COVID-19 pandemic, as compared to before the pandemic. Results indicate that adults <80 years old demonstrated greater increases in technology-based activity, technology-based health communication, and technology-based food acquisition, compared to adults ≥80 years old. Change in in-person communication significantly mediated the relationship between pandemic-related mental health and technology-based communication (standardized coefficient= −0.012; p=.005), and change in in-person activity significantly mediated the relationship between pandemic-related mental health and technology-based activity (standardized coefficient= −0.017; p=.020). Conclusions: This study suggests that older adults are utilizing technology more, and therefore should be considered in technology design and dissemination. Technology use could be an important positive response to help those with pandemic related worries stay safely engaged with friends and family. Technologies should be produced that are modifiable for older adults with disabilities and affordable for older adults with fixed incomes.